EXPLORING THE RELATIONSHIP BETWEEN POLITICAL DISILLUSIONMENT AND THE DESIRE TO MIGRATE ABROAD AMONG THE YOUTH IN RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Migration has become a prevalent phenomenon worldwide, driven by various factors such as economic opportunities, education, and social aspirations. In the context of River State, Nigeria, this research paper explores the intricate relationship between political disillusionment and the desire of youth to migrate abroad. Five hundred and twenty-eight youths (n=528) were conveniently selected from different locations in the River States as the respondents. Data for the survey was collected using a self-report measure assessing political distrust and intention to migrate. Linear regression analysis was conducted on the data, and the result showed that political distrust statistically significantly predicted illegal migration among the youth in River State. The study concludes that political distrust significantly contributes to youth's irregular emigration in River State.